A simplified ductility-based design procedure for seismic retrofit of structures using hysteretic devices. (1st October 2022) - Javidan, Mohammad Mahdi; Kim, Jinkoo
Abstract: The main aim of this study is to derive a simple ductility-based seismic retrofit procedure for buildings using hysteretic devices. In the procedure it is tried to minimize the assumptions while taking more details into consideration compared to previous approaches. With an available seismic retrofit device, the proposed procedure distributes the devices along the height of the structure to satisfy a given performance limit state through a numerical iterative method. The pushover curve and the modal characteristics of the structure are the only required input parameters, and the estimation of the pushover curve after retrofit, its modal characteristics, and maximum interstory drift ratios are byproducts of this procedure. The derived method was applied to seismic retrofit of a case study structure using buckling-restrained braces. The structure was designed to meet the enhanced performance objective of the 1% maximum drift ratio under the Maximum Considered Earthquake level. The nonlinear time history analysis of the structure subjected to 22 pairs of earthquake records showed that the median of the drift ratio demand is 0.8%, satisfying the given limit state. The results show that the proposed procedure can be implemented efficiently in estimating the required amount of seismic retrofit devices and the structural behavior after retrofit. Highlights: A simple ductility-based seismic retrofit procedure for buildings was derived using a numerical iterative method. The proposed procedure distributes the devices along the height of the structure to satisfy a given performance limit state. The derived method is applied to seismic retrofit of a case study structure using buckling-restrained braces. The procedure can estimate the required amount of seismic retrofit devices and the structural behavior after retrofit.